Integration in Ireland : the everyday lives of African migrants - Maguire, Mark; Murphy, Fiona (Manchester : Manchester University Press, 2012)
"The integration of new immigrants is one of the most important issues in Europe, yet not enough is known about the lives of migrants. This book draws on several years of ethnographic research with African migrants in Ireland, many of whom are former asylum seekers. Against the widespread assumptions that integration has been handled well in Ireland and that racism is not a major problem, this book shows that migrants are themselves shaping integration in their everyday lives in the face of enormous challenges. The book will appeal to scholars and students interested in migration and ethnicity and to a general reading public interested in the stories of integration in Ireland. The book is situated within current anthropological theory and makes an important contribution, both theoretically and empirically, to understandings of the everyday and a site of possibility and critique."--Publisher's website.
Taxis, deregulation and racism in Irish border towns -- Inside the politics machine -- Enchanting Ireland -- Hallelujah Halloween -- Miss Nigeria, and emergent forms of life -- Conclusion.
Includes bibliographical references and index.
Keywords: Africans -- Ireland -- Social conditions; Immigrants -- Ireland -- Social conditions; afrikkalaiset; arki; elinolot; etniset suhteet; etnografia; helluntailiike; kotouttaminen (maahanmuuttajat); kotoutuminen (maahanmuuttajat); koululaitos; maahanmuuttajat; monikulttuurisuus; paikallisuus; poliittinen toiminta; rasismi; rituaalit; sosiokulttuuriset tekijät; taksinkuljettajat; turvapaikanhakijat; uskonelämä; afrikaner; vardag; levnadsförhållanden; etniska relationer; etnografi; pingströrelsen; integrationsfrämjande; integration hos invandrare; skolväsen (institution); invandrare; mångkulturalism; lokal anknytning; politisk verksamhet; rasism; ritualer; sociokulturella faktorer; taxichaufförer; asylsökande; trosliv; Ireland -- Ethnic relations; Irlanti; Irland